2011
DOI: 10.1007/s00784-011-0651-7
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils may predict occult lymph node metastasis in early oral cancer

Abstract: The presence of intense TATE is an adjunctive histopathological marker to reinforce the indication of elective neck dissection of the patients with early OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Jain et al evaluated the relationship between histopathologic grading and eosinophil count in metastatic and non-metastatic oral SCC and showed that in well and moderate differentiated metastatic SCC there is a less average eosinophilic count compared to nonmetastatic ones (14). In the current study, there was no relationship between age and gender of the patients with eosinophil count, which was similar to other studies (9,10). However, in the study by Ercan et al, conducted on larynx SCC, there was negative relationship between TATE and age; a decrease in TATE was reported in patients older than 60 years (19).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Jain et al evaluated the relationship between histopathologic grading and eosinophil count in metastatic and non-metastatic oral SCC and showed that in well and moderate differentiated metastatic SCC there is a less average eosinophilic count compared to nonmetastatic ones (14). In the current study, there was no relationship between age and gender of the patients with eosinophil count, which was similar to other studies (9,10). However, in the study by Ercan et al, conducted on larynx SCC, there was negative relationship between TATE and age; a decrease in TATE was reported in patients older than 60 years (19).…”
Section: Discussionsupporting
confidence: 89%
“…Studies showed controversy between eosinophils and effective clinicopathologic factors on prognosis. Some of them reported eosinophils as an independent prognostic factor in OSCC (8) and considered eosinophils as a histopathologic marker to predict early stage lymph node metastasis in patients with OSCC (9). While other studies showed that TATE is not a death risk factor in patients with OSCC (10) and it has no relationship with factors including histopathologic grading and vascular, neural and muscular invasions (11).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated a significant association between high TATE levels and better overall survival . Other studies demonstrated the opposite result, namely, that higher levels of TATE were associated with locoregional recurrence and poorer prognosis . These conflicting results may be explained by inconsistencies in the methods used to measure TATE.…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting results may be explained by inconsistencies in the methods used to measure TATE. These studies used several different proposals and criteria to classify TATE, and TATE levels varied by the methods used to measure the number of eosinophils, intensity and scores, and location of eosinophils within the tumor . The number of eosinophils per high‐power field and the number of eosinophils/square millimeter (density) are the two most commonly used methods to evaluate TATE .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation